Consumer perceptions of Prime bevarages' marketing tools - Lazareva, Varvara; Chytková, Zuzana; Kovářová, Jana; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
The purpose of this thesis is to explore the innovative marketing tactics used by Prime Beverages to stand out in the market and the consumers’ perception of them. It explores the effectiveness of these tactics, in particular by paying close attention to the role of digital marketing and social media on the brand’s success. The research is done through a theoretical analysis and an empirical study involving an online survey among respondents. The findings highlight how strategic social media promotion and influencer endorsements increase consumer engagement and trust, and therefore enhance brand visibility and its’ position in the beverage market. The study suggests that adapting to digital trends and consumer expectations is crucial for brand success.
Vedoucí práce: Zuzana Chytková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses